2021
DOI: 10.1016/j.solener.2021.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Sulfurization temperature effects on crystallization and performance of superstrate CZTS solar cells

Abstract: Kesterite materials based on Cu2ZnSnS4 composition are considered as promising absorber material for the next generation of photovoltaics due to raw materials abundance and low toxicity. Developing a superstrate architecture using kesterite as an absorber could be the key to a better performance, which allows new ways of engineering the formation of a kesterite thin film. In this work, we study the effects of the sulfurization temperature on the crystallization of kesterite film when is fabricated in a superst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Impedance and capacitance–voltage measurements were performed inside a Faraday box with a Biologic impedance analyzer, following the reported literature, , by applying a 20 mV perturbation in a frequency range from 1 GHz to 100 Hz, and applied constant voltage from −0.5 to 1.5 V. EC-lab software was used to fit the equivalent circuits.…”
Section: Methodsmentioning
confidence: 99%
“…Impedance and capacitance–voltage measurements were performed inside a Faraday box with a Biologic impedance analyzer, following the reported literature, , by applying a 20 mV perturbation in a frequency range from 1 GHz to 100 Hz, and applied constant voltage from −0.5 to 1.5 V. EC-lab software was used to fit the equivalent circuits.…”
Section: Methodsmentioning
confidence: 99%
“…However, typical electron selective layers (ETL), such as CdS, have low compatibility with CZTS in a superstrate architecture. 21 Here, a compact or nanostructured thin film of TiO 2 can be adopted as ETL. 22 TiO 2 can act as a stable and protective layer for the FTO while also reducing the risk of shunt paths.…”
Section: Introductionmentioning
confidence: 99%
“…In a superstrate architecture, a wide variety of materials can be tested as a hole transport layer (HTL) and back contact can be probed, which can facilitate the carrier collection at the back surface and can be adapted to semitransparent, bifacial, or tandem solar cells. However, typical electron selective layers (ETL), such as CdS, have low compatibility with CZTS in a superstrate architecture . Here, a compact or nanostructured thin film of TiO 2 can be adopted as ETL .…”
Section: Introductionmentioning
confidence: 99%
“…Others like Borate et al [11], have examined the effect of deposition potential on the composition and morphology of CZTS thin films, whilst Mahjoubi et al [12] reported on the influence of the concentration of Cu in the precursor solution, on some properties of the films. Payno et al [13] published an article on the effect of sulfurization temperature on a CZTS solar cell. These investigations are needed to determine the right synthesis conditions needed for optimum device performance.…”
Section: Introductionmentioning
confidence: 99%